Proceedings of ICC '93 - IEEE International Conference on Communications
DOI: 10.1109/icc.1993.397295
|View full text |Cite
|
Sign up to set email alerts
|

A study on the optimal attributes of transform domain vector quantization for image and video compression

Abstract: It is well known that the optimal transform for scalar quantization is defined as the one that generates completely decorrelated transform coefficients. Under this definition, the Karhunen-Lo&ve transform is optimal and the discrete cosine transform is close to optimal. However, if vector quantization (VQ) is used in the transform domain, such a definition is no longer appropriate because compression performance of VQ is actually better when the components within the vector are more correlated. Therefore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In real life, video images are vector-valued signals. Vector transforms have been recently studied for image coding by Li [5][6] , where input signals are finite vectors with same dimension and it has been shown that vector transforms have advantage in image coding at low bit rates. Another type of vector transforms has been discussed in [7].…”
Section: Introductionmentioning
confidence: 99%
“…In real life, video images are vector-valued signals. Vector transforms have been recently studied for image coding by Li [5][6] , where input signals are finite vectors with same dimension and it has been shown that vector transforms have advantage in image coding at low bit rates. Another type of vector transforms has been discussed in [7].…”
Section: Introductionmentioning
confidence: 99%
“…Vector transforms have been recently introduced for image coding by , where input and output signals are nite vectors with same dimension. It was shown that vector transforms have advantage in image coding at low bit rates [3][4][5][6]. Moreover, vector quantization can be applied more easily in the vector transform domain than in the conventional scalar transform domain.…”
Section: Introductionmentioning
confidence: 99%
“…2 R. For more details, see[19][20][21][22]. In particular, if the interpolant in (4.1) is identical to the scaling function , the sampling formula(4In this case, we call that (t) is a scaling function with sampling property(or cardinal orthogonal scaling function (COSF), see 22]). It is clear 22] that a scaling function (t) is with sampling property if and only if (It was also shown in 24] that under certain regularity condition (4.4) is true if and only if h 0 = 0:5; h 2k = 0 for k 6 = 0; (4.5)where h k is the impulse response of the quadrature mirror lter H(!)…”
mentioning
confidence: 99%